Synthesis of planar conjugated macrocycle by secondary ketimine formation between m-phenylenediamine and synthesised aryl diketone - Huo, Jiongrui (2015)
Synthesis-driven approaches are powerful methods that can be employed to create new and functional materials, forming strategies to create a material with desired properties based on structure-property relationships. In this project, such an approach was attempted to create a novel discotic macrocycle possessing self-assembly and charge carrier transport capabilities. Synthesis was attempted via a two-step strategy: single-step synthesis of a diketone to control the peripheral alkyl chain length, followed by single-step secondary ketimine condensation between 1,3-phenylenebis((4-octylphenyl)methanone) and m-phenylenediamine. While synthesis of the diketone was successful, synthesis of the target macrocycle was not, despite repeated attempts in a variety of solvent systems, azeotropic distillation to remove water, and in harsh reaction conditions. This was likely due to the stability of the C=O bond and steric hindrance against nucleophilic attack on the carbon atom of the carbonyl group of the diketone. It is thus recommended for future researchers attempting discotic imine macrocycle synthesis to do so with less sterically hindered alkylated dialdehydes and diamines to produce secondary aldimines instead, with possible preparation methods outlined in the literature review section of this report.